Dual chiral silver catalyst in the synthetic approach to the core of hepatitis C virus inhibitor GSK 625433 using enantioselective 1,3-dipolar cycloaddition of azomethine ylides and electrophilic alkenes - Chabour, Ihssene (2017)
The asymmetric 1,3-dipolar cycloaddition of an imino ester 5 with tert-butyl acrylate is catalyzed by a dual chiral silver(I) complex formed from a chiral phosphoramidite 14 and the chiral silver(I) binolphosphate (R)-17. This reaction is selected to achieve the synthesis of enantiomerically enriched key structures to access the third generation of GSK HCV inhibitors. The scope of this dual chiral catalytic system is analyzed by employing different imino esters and dipolarophiles, and also compared with the same cycloaddition reactions performed with the chiral phosphoramidite 14·AgClO4 complex.